Innovative approaches in the teaching methodology of preschool education of bilingual children - T M Balykhina; O V Veter; I Ya Chernyaeva (Polylinguality and Transcultural Practices, 2014)
The article is devoted to analysis of modern provision of preschool education of bilingual children. Identified scientific approaches to innovation in preschool education, to formation of a technique of training of bilingual children. Examines current trends in modern preschool education.